Early recognition of sepsis-induced coagulopathy using the C2PAC index: a ratio of soluble type C lectin-like receptor 2 (sCLEC-2) level and platelet count. (18th August 2022) - Ishikura, Hiroyasu; Irie, Yuhei; Kawamura, Masahide; Hoshino, Kota; Nakamura, Yoshihiko; Mizunuma, Mariko; Maruyama, Junichi; Nakashio, Maiko; Suzuki-Inoue, Katsue; Kitamura, Taisuke
Abstract: C-type lectin-like receptor 2 (CLEC-2) is a platelet-activated receptor expressed on the surface of platelet membranes. Soluble CLEC-2 (sCLEC-2) has been receiving attention as a predictive marker for thrombotic predisposition. The present study examined the relationship between sCLEC-2 level and degree of coagulation disorder in septic patients. Seventy septic patients were divided into the sepsis-induced disseminated intravascular coagulation (DIC) (SID) group (n = 44) and non-SID group (n = 26). The sCLEC-2 levels were compared between the two groups. Because we suspected that the sCLEC-2 level was affected by the platelet count, we calculated the sCLEC-2/platelet count ratio (C2PAC index). We further divided septic patients into four groups using the Japanese Association for Acute Medicine (JAAM) DIC scoring system (DIC scores: 0–1, 2–3, 4–5, and 6–8). The C2PAC index was significantly higher in the SID group (2.6 ± 1.7) compared with the non-SID group (1.2 ± 0.5) ( P < .001). The C2PAC indexes in the four JAAM DIC score groups were 0.9 ± 0.3, 1.1 ± 0.3, 1.7 ± 0.7, and 3.6 ± 1.0, respectively, and this index increased significantly as the DIC score increased ( P < .001). According to the receiver-operating curve analysis, the area under the curve (AUC) and optimal cutoff value for the diagnosis of SID were 0.8051 and 1.4 (sensitivity, 75.0%; specificity, 76.9%), respectively. When the C2PAC index and D-dimer level, one of the main fibrinolytic markers, were selected as predictive markers for SID diagnosis in stepwise multiple logistic regression analysis, it was possible to diagnose SID with a high probability (AUC, 0.9528; sensitivity, 0.9545; specificity, 0.8846). The C2PAC index is a useful predictor of SID progression and diagnosis in septic patients.